The Relationship of The Delivery Process to The Risk of Postpartum Depression at RSIA Pucuk Permata Hati - Ni Putu Ika Santiari; Luh Putu Widiastini; Ni Putu Mirah Yunita Udayani (Fakultas Kedokteran, 2022)
Background : Pregnancy and childbirth are periods of life full of potential stress. A woman in the period of pregnancy and the postpartum period tends to experience considerable stress due to limited physical conditions that make her have to limit activities and undergo the process of adaptation to become a mother. This period has the potential for postpartum depression. This study aims to determine the relationship between postpartum depression in mothers who gave birth normally and mothers who gave birth through Sectio Caesarea. Methods: The research subjects were 30 mothers who gave birth and experienced postpartum depression at Pucuk Permata Hati Hospital. This study used the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. The data were analyzed by statistical product and service solution (SPSS) using the chi square test method. Results: The prevalence of postpartum depression at RSIA Pucuk Permata Hati using EPDS scoring, most of the respondents who experienced postpartum depression were 26 people (72.2%) through cesarean section and 4 people (16.7%) went through normal delivery. Conclusion: The significance value obtained is 0.000 so that the p value <0.05. This indicates that there is a significant relationship between the delivery process and the risk of postpartum depression at RSIA Pucuk Permata Hati. The OR value was found to be 13, which indicates that respondents who delivered caesarean section had a 13 times chance of experiencing depression.